Intelligent System for the Management of Resources Dedicated to Humanity - Khoulji, Samira; Chouya, S.; Bourekkadi, S.; Slimani, K.; Kerkeb, M.L. (Transactions on Engineering and Computing Sciences, 2017)
Our work consists, one way or another, in projecting the light on the intensive need for the reasonable management of water resources. According to the latest studies and statistics, Morocco will soon face a serious crisis if it has not taken the necessary precautions and decisions to deal with the dangers linked to water resources. The solution we have developed is not costly at the material / financial level, since it does not imply to the client to have a smartphone or an internet connection, but precisely the possession of the client or other members Of his family of a mobile phone of whatever nature. From this we can assume that our solution adopts the communication network technology of mobile phones without imposing exclusivity on a company without others and that will be totally free. Among the positive results that our work will bring is the creation of an atmosphere of relaxation and satisfaction among the citizens, through continuous communication and interaction with them, to make them more satisfied with the quality of services. Moreover, this solution is one of the policies that call for the preservation of water resources and the restoration of citizens’ confidence in drinking water companies, and on the other hand we will contribute to the positif use of Technology and modern means of communication, and the humanization of our information systems. To conclude, we believe that these ideas will have a favorable influence on all poles, whether citizens, countries or future generations.